MetricRA: Learning Software Metrics through Augmented Reality - Motta, Rebeca; Bonicenha, Mario; Rodrigues, Claudia Susie; Werner, Cláudia (Anais do Workshop sobre Educação em Computação (WEI); 2018: Anais do XXVI Workshop sobre Educação em ComputaçãoDO - 10.5753/wei.2018.3508, 2018)
Augmented reality creates a bridge between virtual and real world, providing stimulating resources for different purposes. This technology enables new teaching possibilities since it can bring more abstract concepts into reality and put the knowledge related to several areas, such as Software Engineering, into practice. MetricRA is a tool developed to help Software Engineering students to understand Cohesion and Coupling metrics. The solution was implemented with Augmented Reality technology, where the user can control a class diagram to observe the metrics transformation. This article describes MetricRA tool and presents a study conducted to evaluate its ability to contribute to the understanding of the concepts proposed.